Association of Gene Polymorphisms with Polycystic Ovary Syndrome: A Meta-analysis - G. P. Abinaya; B K Iyshwarya; Ramakrishnan Veerabathiran (Wolters Kluwer Medknow Publications, 2024)
Objectives: Polycystic ovary syndrome (PCOS) is a prevalent endocrine-metabolic disorder affecting reproductive-aged women. Genetic factors play a significant role in its development. This meta-analysis assesses the associations between specific gene polymorphisms (Vitamin D receptor [VDR] and adiponectin [ADIPOQ]) and PCOS susceptibility. Materials and Methods: We conducted a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, Collecting data from published articles between 2013 to 2013. Eligible studies were selected based on inclusion and exclusion criteria, with quality assessment performed using the Newcastle-Ottawa scale. Data were extracted, and statistical analyses included odds ratios with 95% confidence intervals for gene polymorphisms. Heterogeneity was evaluated using I2 tests, and publication bias was assessed using Begg's and Egger's tests. Results: A total of 33 articles involving 5677 cases and 5257 controls were included in the analysis. Significant associations were observed for VDR TaqI rs731236 polymorphism in the dominant and recessive models and VDR BsmI rs1544410 polymorphism in the dominant and recessive models. For ADIPOQ T45G rs2241766, a significant association was found in the heterozygous model. The results did not reveal any significant associations for ADIPOQ G276T rs1501299. Conclusion: This meta-analysis suggests associations between specific gene polymorphisms (VDR and ADIPOQ) and PCOS susceptibility. Further research is needed to validate these findings and unravel the complex genetic factors contributing to PCOS, potentially leading to improved diagnostic and therapeutic strategies.